Effect of protein oxidation on the impaired quality of dry-cured loins produced from frozen pork meat. (1st April 2016) - Lorido, Laura; Ventanas, Sonia; Akcan, Tolga; Estévez, Mario
Highlights: Freezing prior to processing increased protein oxidation in dry-cured loins. Freezing also had consequences on the sensory properties of the final product. Cross-linking via carbonylation pathway may have caused meat strengthening. Abstract: Dry-cured loins elaborated from frozen (−20 °C/20 weeks)/thawed longissimus dorsi muscles (F) were compared with counterparts elaborated from fresh (unfrozen) muscles (UF) for the extent of protein oxidation (carbonylation and Schiff base formation) and their sensory profile (quantitative–descriptive analysis). All samples had similar moisture, fat and protein contents ( p  > 0.05). In accordance with previous studies, freezing meat prior to processing affected the oxidative stability of meat proteins. This chemical change occurred concomitantly with modifications of the sensory profile of the loins as F-samples received significantly ( p  < 0.05) higher scores for rancid and salty flavor, hardness and fibrousness than UF-counterparts. The formation of cross-links (assessed as Schiff bases) during freezing and the subsequent processing may have contributed to strengthening the meat structure and hence, impairing the texture properties of dry-cured loins.